Response of Fish and Invertebrate Larvae to Backreef Sounds at Varying Distances: Implications for Habitat Restoration - Emily R. Anderson; Jack Butler; Mark J. Butler (Frontiers in Marine Science, 2021)
Underwater sound is used by many marine larvae to orient to coastal habitats including backreef, sponge-dominated hardbottom habitat in the Florida Keys (FL, United States)—a particularly “noisy” coastal habitat. However, the distance over which acoustic cues are attractive to settlement-stage larvae is generally unknown. We examined this phenomenon in a region of the Florida Keys where mass sponge die-offs have diminished both underwater soundscapes and larval settlement. The absence of pronounced hardbottom-associated sound over such a large area allowed us to experimentally test in situ the response of fish and invertebrate larvae to broadcasted sounds at different distances from their source. We first measured the signal-to-noise ratio of healthy hardbottom habitat soundscapes broadcast from an underwater speaker at seven distances to determine the maximum range of the signal. Based on those results, larval collectors were then deployed at 10, 100, 500, and 1,000 m from speakers broadcasting sounds recorded at either degraded or healthy hardbottom sites for five consecutive nights during each of three new and full moon periods in summer/fall 2019. Larval settlement onto those collectors was affected by lunar phase and soundscape type, but varied among species. In most cases, the effect was small and not likely to be ecologically significant. The absence of a strong larval settlement response to a sound cue lies in contrast to results from other studies. We suspect that the small (<500 m) radius of the broadcasted soundscapes may have limited the magnitude of the larval response to locally available larvae whose abundance may have been low because the experiment was conducted within a large, relatively quiet seascape. If true, it is possible that planktonic larvae may require a series of acoustic “sign-posts,” perhaps in combination with other cues (e.g., chemical), to successfully orient to distant nursery habitats. Although habitat restoration efforts may be able to restore healthy soundscapes, the typically small size and number of restoration sites may limit the range of the acoustic cue and thus larval attraction to restored habitats.